2022
DOI: 10.1055/s-0042-1755561
|View full text |Cite
|
Sign up to set email alerts
|

Language Assessment in Patients with Disorders of Consciousness

Abstract: The assessment of residual language abilities in patients with disorders of consciousness (DoC) after severe brain injury is particularly challenging due to their limited behavioral repertoire. Moreover, associated language impairment such as receptive aphasia may lead to an underestimation of actual consciousness levels. In this review, we examine past research on the assessment of residual language processing in DoC patients, and we discuss currently available tools for identifying language-specific abilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
0
2
0
Order By: Relevance
“…Active and passive paradigms in using fMRI and EEG have demonstrated utility in identifying CMD in behaviorally unresponsive patients. However, it has been found that passive paradigms have a greater likelihood of capturing preserved consciousness ( Kondziella et al, 2016 ; Aubinet et al, 2022 ). The scientific understanding of CMD is evolving, but current evidence suggests it is likely a distinct phenomenon separate from the DoC spectrum ( Kondziella and Stevens, 2022 ), more akin to a functionally locked-in syndrome.…”
Section: Neurobehavioral Assessment Across Care Settings: Impact Of C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Active and passive paradigms in using fMRI and EEG have demonstrated utility in identifying CMD in behaviorally unresponsive patients. However, it has been found that passive paradigms have a greater likelihood of capturing preserved consciousness ( Kondziella et al, 2016 ; Aubinet et al, 2022 ). The scientific understanding of CMD is evolving, but current evidence suggests it is likely a distinct phenomenon separate from the DoC spectrum ( Kondziella and Stevens, 2022 ), more akin to a functionally locked-in syndrome.…”
Section: Neurobehavioral Assessment Across Care Settings: Impact Of C...mentioning
confidence: 99%
“…Although outside the scope of this paper, there are tools available for assessing agitation, confusion, attention, orientation, language and communication in persons with DoC demonstrating MCS+ or emergence behaviors. These assessments can include the Confusion Assessment Protocol, Agitated Behavior Scale, Orientation Log and the Loewenstein Communication Scale ( Bogner et al, 1999 ; Sherer et al, 2005 ; Frey et al, 2007 ; Spiteri et al, 2021 ; Aubinet et al, 2022 ). Figure 1 presents an overview of recommended strategies to optimize the patient and environment to ensure accuracy of assessment results.…”
Section: Practical Strategies For Optimizing Neurobehavioral Assessme...mentioning
confidence: 99%